Membangun Pemahaman Terhadap Tujuan Pembangunan Berkelanjutan Dan Indikator Global Sustainable Tourism Council - Roseven Rudiyanto; Septian Hutagalung; Fitri Ciptosari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
The development of tourism has a negative impact on the environment of new management practices in the tourism industry, namely tourism villages. Tourism villages are also a form of implementing sustainable development goals. As one of the tourist villages in West Manggarai Regency, Wae Lolos Village must be able to be managed into a tourism village that is following the goals of sustainable development, so it is essential to manage a tourist village that understands the management of a tourist village under the goals of sustainable development. There are public lectures, pre-and post-tests, and self assessment using the global sustainable tourism council criteria in community service activities—Results of increasing mean value between the pre-test and post-test indicate the understanding of sustainable development goals. In addition, based on the GSTC aspect of the destination category, the aspect of governance is the aspect that has the most percentage of met criteria, but environmental aspects are the aspects that have presentation criteria. Wae Lolos Village uses the GSTC criteria as a measuring tool for monitoring and evaluating the performance of tourism villages.